Synthetic Oxytocin and Vasopressin Act Within the Central Amygdala to Exacerbate Aggression in Female Wistar Rats - Oliveira, Vinícius E. de M.; de Jong, Trynke R.; Neumann, Inga D. (Frontiers in Neuroscience, 2022)
Exacerbated aggression is a high-impact, but poorly understood core symptom of several psychiatric disorders, which can also affect women. Animal models have successfully been employed to unravel the neurobiology of aggression. However despite increasing evidence for sex-specificity, little is known about aggression in females. Here, we studied the role of the oxytocin (OXT) and vasopressin (AVP) systems within the central amygdala (CeA) on aggressive behavior displayed by virgin female Wistar rats using immunohistochemistry, receptor autoradiography, and neuropharmacology. Our data show that CeA GABAergic neurons are activated after an aggressive encounter in the female intruder test (FIT). Additionally, neuronal activity (pERK) negatively correlated with the display of aggression in low-aggressive group-housed females. Binding of OXT receptors, but not AVP-V1a receptors, was increased in the CeA of high-aggressive isolated and trained (IST) females. Finally, local infusion of either synthetic OXT or AVP enhanced aggression in IST females, whereas blockade of either of these receptors did not affect aggressive behavior. Altogether, our data support a moderate role of the CeA in female aggression. Regarding neuropeptide signaling, our findings suggest that synthetic, but not endogenous OXT and AVP modulate aggressive behavior in female Wistar rats.